European exchange rate adjustments in response to Covid-19, containment measures and stabilization policies - Jens Klose (Philipps-University Marburg, School of Business and Economics, 2022)
This paper estimates the effects of nine exchange rates for european coun- tries vis-a-vis the Euro in the COVID pandemic. Using data on COVID cases, three containment and two stabilization measures relative to the euro area counterparts, it is shown that a more severe spread of the virus leads to a depreciation of the domestic currency. The same holds with respect to stricter movement restrictions, health care measures and more supportive monetary policies. More expansionary fiscal policies by the domestic country on the other hand lead to an appreciation of the currency. Two extensions show that the results differ with respect to whether the country is a scandinavian or eastern european country and whether the euro area countries or the other european countries introduce the measures.
Keywords: E44; E52; E62; 330; Exchange rates; COVID-19; Europe; stabilization policies; containment measures; panel VAR